Recovery following long-haul international travel in team sport athletes - Fowler, P. M. (ASPETAR Sports Medicine Journal, 2015)
Since elite team sport athletes regularly undertake long-haul international travel, recovery from travel is important for ensuing training and competition success. However, due to an insufficient understanding of the impact of travel on sports performance, there is a paucity of related evidencebased interventions. Therefore, this article will highlight the potential mechanisms through which international travel may affect team sport performance and provide practical and evidence-based guidelines for coaches and sports medicine practitioners to implement around travel.